PERLINDUNGAN HUKUM PEMEGANG HAK CIPTA ATAS LAGU VIRGOUN YANG DIUNGGAH PADA APLIKASI TIKTOK - Yudhistira, Bagaskara Yudha; Riswandi, Budi Agus (Fakultas Hukum Universitas Islam Indonesia, 2022)
TikTok is one of the most popular social networking applications and music video platforms in the world. TikTok also uses a lot of songs or music from various creators, this creates legal problems, especially in the field of copyright for song or music creators, namely the distribution of copyright- related products without permission/licence. So that it violates the rights related to copyright and the economic rights of the creator. This study uses a juridical-normative legal research method which is a legal research that is literature writing in the form of books, journals, and regulations that have a correlation to the discussion of problems, and with a legal approach and uses a conceptual approach by examining the doctrine of experts related to the legal issues under study. The application's liability to the copyright holder of the song or music is in the form of compensation or termination of the distribution or reproduction of related products whose copyright is violated. The protection given to song or music copyright holders is criminally and civilly against copyright law violations in accordance with Law Number 28 of 2014 concerning Copyright.